Types of contraceptive methods - Alicja Konieczna; Marta Czapiewska; Jerzy Krysiński (Polish Pharmaceutical Society, 2020)
The term contraception can be used to define a set of methods that control fertility as well as help conscious family planning. The growing interest in the subject of contraception methods, which are used by majority of women today, cause that there are more and more ways of fertility regulation. In this paper are presented the most common contraceptive methods, taking into account the effectiveness of a given method, contraindications, side effects and the mechanism of action. The Pearl Index indicates failure rate of the use of a given contraceptive method, i.e. it allows to determine the number of pregnancies in a group of 100 women using a given contraceptive method within one year. It is still a frequently used way of comparing the effectiveness of different contraceptive methods. Most of the available methods are based on the use of synthetic hormones from the group of progestins and estradiol derivatives in the form of combinened oral contraceptive pills, mini-pills, patches, intramuscular injections, vaginal rings, implants, intrauterine devices (IUDs with hormones - levonorgestrel and without hormones, copper). Combined contraceptive pills are very popular, especially among sexually active young women. Despite their lower effectiveness, mini-pills tablets are often used by women who, for various reasons, cannot use ethinylestradiol derivatives. The undoubted advantage of vaginal rings, contraceptive patches and intramuscular injections is the lack of a daily regimen of their use. IUDs are most often chosen by women who do not plan pregnancy in the next few years. Natural methods were also examined, the greatest effectiveness of which, confirmed by the Pearl Index, is based on the use of cycle computers. The biggest limitation of these cycle computers is their high price. Mechanical methods and less frequently used spermicides are also discussed. Contraceptive methods should characterize a broad safety profile, be low-priced, easily accessible and their effects should be fully reversible. Despite of the various available forms of contraception nowadays, there still is no method which would match all of the above given criteria.